Indirect Competitive Aptamer-Based Enzyme-Linked Immunosorbent Assay (apt-ELISA) for the Specific and Sensitive Detection of Isocarbophos Residues. (13th August 2019) - Xiang, Li; Wu, Huanle; Cui, Zhaoxing; Tang, Jianshe
Abstract: Environmental contamination from pesticide residues is a worldwide public health concern and has attracted increasing attention from researchers over the past several years. In this study, an aptamer-based enzyme-linked immunosorbent assay (apt-ELISA) using enzyme signal amplification has been developed to determine isocarbophos residues. The limit of detection for the apt-ELISA was 0.05 ng/mL for isocarbophos, and the sensitivity was better than that obtained using the traditional ELISA approach. The average recovery of the apt-ELISA ranged from 84 to 97%, and the coefficient of variation ranged from 4.6 to 12.1% when determining the isocarbophos residues in various water samples. The results demonstrate that the proposed approach can be used for routine screening of isocarbophos residues.